Detailed investigation of the composition and transformations of phenolic compounds in fresh and fermented Vaccinium floribundum berry extracts by high‐resolution mass spectrometry and bioinformatics. Issue 4 (21st January 2022) - Cerrato, Andrea; Piovesana, Susy; Aita, Sara Elsa; Cavaliere, Chiara; Felletti, Simona; Laganà, Aldo; Montone, Carmela Maria; Vargas‐de‐la‐Cruz, Celia; Capriotti, Anna Laura
Abstract: Introduction: Blueberries are known for their very high content of biologically active phenolic compounds; nonetheless, differently from the North American and European species of blueberries, Neotropical blueberries have not been extensively studied yet. Objectives: In the present paper, the phenolic composition of Vaccinium floribundum Kunth, which is endemic to the Andean regions and grows 1, 600 to 4, 500 meters above sea level, was investigated by ultra‐high‐performance liquid chromatography coupled to high‐resolution mass spectrometry (UHPLC‐HRMS). Native and fermented berries were compared in terms of phenolic composition as well as antioxidant activity, total phenolic content, and total anthocyanin content. Materials and Methods: V. floribundum native and fermented berries were extracted and analyzed by UHPLC‐HRMS. The acquired datasets were processed by Compound Discoverer 3.1 using a dedicated data analysis workflow that was specifically set up for phenolic compound identification. Results: In total, 309 compounds were tentatively identified, including anthocyanins, flavonoids, phenolic acids, and proanthocyanidins. The molecular transformations of phenolic compounds during fermentation were comprehensively investigated for the first time, and by a customized data processing workflow, 13 quinones and quinone methides were tentatively identified in the fermented samples. Compared to other species of the genus Vaccinium, a peculiar phenolic profile is observed, with low abundance of highly methylated compounds. Conclusion: Andean berries are a rich source of a wide variety of phenolic compounds. Untargeted MS analyses coupled to a dedicated data processing workflow allowed expanding the current knowledge on these berries, improving our understanding of the fate of phenolic compounds after fermentation. Abstract : In the present paper, the phenolic composition of Vaccinium floribundum Kunth (endemic to the Andean regions) was investigated by ultra‐high‐performance liquid chromatography coupled to high‐resolution mass spectrometry; 309 compounds were tentatively identified. After lactic fermentation, fresh and fermented berries were compared in terms of antioxidant activity, total phenolic content, and total anthocyanin content. Moreover, the molecular transformations of phenolic compounds during fermentation were comprehensively investigated for the first time, providing the tentative identification of 13 quinones and quinone methides.